2016
DOI: 10.1021/acs.jnatprod.6b00362
|View full text |Cite
|
Sign up to set email alerts
|

Quambalarine B, a Secondary Metabolite from Quambalaria cyanescens with Potential Anticancer Properties

Abstract: Quambalarine B (QB) is a secondary metabolite produced by the basidiomycete Quambalaria cyanescens with potential anticancer activity. Here we report that QB at low micromolar concentration inhibits proliferation of several model leukemic cell lines (Jurkat, NALM6, and REH), whereas higher concentrations induce cell death. By contrast, the effect of QB on primary leukocytes (peripheral blood mononuclear cells) is significantly milder with lower toxicity and cytostatic activity. Moreover, QB inhibited expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…As a potential result of high AMP levels, we confirmed a decrease in O-glycosylation of proteins, which was represented as an important regulator of stability of several oncogenic factors such as C-MYC. Consistent with this hypothesis, C-MYC levels were significantly downregulated during QB treatment [ 24 ]. Hence, inhibition of hexosamine pathway and protein O-glycosylation provided a new possibility to regulate leukemia cells proliferation [ 41 ].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…As a potential result of high AMP levels, we confirmed a decrease in O-glycosylation of proteins, which was represented as an important regulator of stability of several oncogenic factors such as C-MYC. Consistent with this hypothesis, C-MYC levels were significantly downregulated during QB treatment [ 24 ]. Hence, inhibition of hexosamine pathway and protein O-glycosylation provided a new possibility to regulate leukemia cells proliferation [ 41 ].…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, serine represents one of the end-point glycolysis-derived metabolites and allosterically activates PKM2 activity [ 34 ]. We have previously demonstrated that QB treatment decreases C-MYC protein levels and PKM2 mRNA levels in several leukemic cells [ 24 ]. In this study, we also demonstrated an increase in the serine levels after QB treatment; hence, we tested PKM activity after QB treatment using enzymatic assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to increased pyruvic acid and decreased lactic acid levels. To inhibit mitochondrial complex I activity, quambalarine B inhibits folic Quambalarine B ( 57) is a natural naphthoquinonic compound from Quambalariac yanescens [115]. It inhibited the activity of mitochondrial complex I and II and reduced the metabolism of aspartic acid and folic acid as therapeutic targets in Jurkat cells.…”
Section: Quinonesmentioning
confidence: 99%